Understories : The Political Life of Forests in Northern New Mexico - Kosek, Jake (Book collections on Project MUSE., 2006)
A lively, engaging ethnography that demonstrates how a volatile politics of race, class, and nation animates the infamously violent struggles over forests in the U.S. Southwest